Single nucleotide polymorphisms in latex biosynthesis genes in high yielding RRII 400 series rubber clones - Saha T; Bini K; Madhavan A; Ravindran M; Roy C B; Thomas K U (IRRDB Natural Rubber Conference 2008, 13-15 October 2008, Kuala Lumpur, Malaysia: Abstract of papers)
DL
Source Year: 2008
Keywords: Latex biosynthesis gene; Single nucleotide polymorphisms(SNPs)